Generating models of anisotropic compact stars - Jangid, Ankita; Ratanpal, B. S.; Venkataratnam, K. K. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We consider two generators $z$ that describe metric potential $g_{rr}$ and the equation of state used to generate models of anisotropic compact stars in the static spherically symmetric space-time metric. In particular, we take a specific value of $z$ and the linear equation of state and generate the solutions. The model is found to be well-behaved and results are examined for the 4U 1820-30 star. Moreover, the generators of several well-known models are described.